Dietary transition difficulties in preterm infants: critical literature review - Carla Lucchi Pagliaro; Karina Elena Bernardis Bühler; Silvia Maria Ibidi; Suelly Cecília Olivan Limongi (Elsevier, 2016)
ABSTRACT OBJECTIVE: To analyze the scientific literature on dietary changes in preterm children during the first years of life. DATA SOURCE: The PubMed database was used for article selection. The texts were analyzed according to their objectives, research design, and research group characteristics. The following were selected to comprise the criteria: (1) publications in the period from 1996 to 2014; (2) participation of infants and children from birth to 10 years of age; (3) development of oral motor skills necessary for feeding; (4) development of the feeding process; and (5) feeding difficulties during childhood. SUMMARY OF THE FINDINGS: There were 282 studies identified, of which 17 were used in the review, and five more articles were identified through the reference list of selected articles, totaling 22 references. CONCLUSION: Very low birth weight preterm newborns are more likely to have feeding problems in early postnatal stages and during childhood when compared with full-term infants. Monitoring the feeding of these infants after hospital discharge is strictly recommended in an early intervention program aiming at better development of feeding skills.